KESANTUNAN BERBAHASA PERSPEKTIF LEECH DALAM DIALOG LINTAS AGAMA: STUDI KASUS HABIB HUSEIN JA’FAR DAN PENDETA MARCEL - Susanto, Rahmad Nanda Viky Susanto (Jurnal PENEROKA, 2024)
Dialogue between religious leaders is often debated on social media due to a lack of understanding of politeness in language. Language politeness is one of the studies found in pragmatics. In this regard, the purpose of this study is to describe the language politeness contained in the dialog between Islamic religious leaders Habib Ja'far and Pastor Marcel. The study in this research uses a qualitative descriptive approach. The data taken from this research comes from the dialog speech of language politeness performed by the two religious figures. The data source in this research is Deddy Corbuzier's YouTube link Login segment. Listening and reading techniques are data collection techniques used by researchers. Data analysis in this study uses data reduction, data presentation, and conclusion drawing. The results of this study found the existence of the principle of language unity cooperation on the maxims of wisdom, generosity, praise, sympathy, and humility that have been carried out by two religious figures as objects.